Mechanisms of Maggot-Induced Wound Healing: What Do We Know, and Where Do We Go from Here?. (13th March 2014) - Sherman, Ronald A.
Abstract : Medicinal maggots are believed to have three major mechanisms of action on wounds, brought about chemically and through physical contact: debridement (cleaning of debris), disinfection, and hastened wound healing. Until recently, most of the evidence for these claims was anecdotal; but the past 25 years have seen an increase in the use and study of maggot therapy. Controlled clinical studies are now available, along with laboratory investigations that examine the interaction of maggot and host on a cellular and molecular level. This review was undertaken to extract the salient data, make sense, where possible, of seemingly conflicting evidence, and reexamine our paradigm for maggot-induced wound healing. Clinical and laboratory data strongly support claims of effective and efficient debridement. Clinical evidence for hastened wound healing is meager, but laboratory studies and some small, replicated clinical studies strongly suggest that maggots do promote tissue growth and wound healing, though it is likely only during and shortly after the period when they are present on the wound. The best way to evaluate—and indeed realize—maggot-induced wound healing may be to use medicinal maggots as a "maintenance debridement" modality, applying them beyond the point of gross debridement.